The busy periphery : urban systems of the Balkan and Danube Provinces (2nd-3rd c. AD) - Donev, Damjan, 1979- (Archaeopress Roman archaeology, 2019)
The Busy Periphery: Urban Systems of the Balkan and Danube Provinces (2nd - 3rd c. AD) considers the reconstruction of the urban geography of the Balkan and Danube provinces at the time of the Severan dynasty. Four basic parameters governed the focus of research: the origin and socio-economic character of the settlements, their size, micro-location, and the size of their administrative territories. The principal goal was to map the variable developments of the urban network, both between and within the sub-regions that constituted this part of the Roman Empire.